Measurement of 107-MeV proton-induced double-differential thick target neutron yields for Fe, Pb, and Bi using a fixed-field alternating gradient accelerator at Kyoto University. Issue 4 (3rd April 2023) - Iwamoto, Hiroki; Nakano, Keita; Meigo, Shin-Ichiro; Satoh, Daiki; Iwamoto, Yosuke; Sugihara, Kenta; Nishio, Katsuhisa; Ishi, Yoshihiro; Uesugi, Tomonori; Kuriyama, Yasutoshi; Yashima, Hiroshi; Okabe, Kota; et al.
ABSTRACT: Double-differential thick target neutron yields (TTNYs) for Fe, Pb, and Bi targets induced by 107-MeV protons were measured using the fixed-field alternating gradient accelerator at Kyoto University for the research and development of accelerator-driven systems (ADSs) and fundamental ADS reactor physics research at the Kyoto University Critical Assembly (KUCA). Note that TTNYs were obtained with the time-of-flight method using a neutron detector system comprising eight neutron detectors; each detector has a small EJ-301 liquid organic scintillator and photomultiplier tube. The TTNYs obtained were compared with calculation results using Monte Carlo-based spallation models (i.e. INCL4.6/GEM, Bertini/GEM, JQMD/GEM, and JQMD/SMM/GEM) and the evaluated high-energy nuclear data library, i.e. JENDL-4.0/HE, implemented in the particle and heavy ion transport code system (PHITS). All models, including JENDL-4.0/HE, failed to predict high-energy peaks at a detector angle of 5 ∘ . Comparing the energy- and angle-integrated spallation neutron yields at energies of ≤20 MeV estimated using the measured TTNYs and the PHITS indicated that INCL4.6/GEM would be suitable for the Monte Carlo transport simulation of ADS reactor physics experiments at the KUCA. Graphical Abstract: uf0001